Global trends in educational activities of sports universities - Lubysheva L.I.; Rosenko S.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to pinpoint the key patterns and trends in the networking activities of Russian sports universities in the context of international expansion. Methods and structure of the study. The examination of the key indicators of international educational and research activities in Russian institutions of higher learning specializing in physical education and sports is conducted. Results and conclusions. Currently, the development of the international activities of Russian sports universities is characterized by new trends reflecting the specifics of the modern educational and scientific space. These include the implementation of online educational programs as a tool for building a unified educational trajectory of partner universities, the internationalization of scientific activities, the formation of an intra-university socio-cultural environment, etc. Collectively, these areas lead to an increase in the educational and scientific status of Russian sports universities and their international competitiveness.